2017
DOI: 10.1016/j.pharep.2016.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alpha-lipoic acid on expression of iron transport and storage proteins in BV-2 microglia cells

Abstract: ALA could up-regulate TfR1, DMT1 and ferritin expression when iron is increased outside of the cell, promoting iron deposition into ferritin by increasing cell iron uptake, and then reducing free iron both inside and outside of the cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Both iron import and ferritin expression increased following silica exposure of the AMs. Such increased expression of both iron importers and ferritin has been observed previously and is possibly accounted for by temporal disparities in the expression of the proteins. Particles initially bind cell iron decreasing availability of the metal. Increased import (e.g., transport by divalent metal transporter 1) is proposed to follow, and this would reverse metal deficiency, elevate availability of the metal, and subsequently enhance the expression of storage proteins (e.g., ferritin).…”
Section: Discussionmentioning
confidence: 52%
“…Both iron import and ferritin expression increased following silica exposure of the AMs. Such increased expression of both iron importers and ferritin has been observed previously and is possibly accounted for by temporal disparities in the expression of the proteins. Particles initially bind cell iron decreasing availability of the metal. Increased import (e.g., transport by divalent metal transporter 1) is proposed to follow, and this would reverse metal deficiency, elevate availability of the metal, and subsequently enhance the expression of storage proteins (e.g., ferritin).…”
Section: Discussionmentioning
confidence: 52%
“…Within cells, ferritin serves as the primary complex responsible for iron storage, playing a crucial role in iron homeostasis. Consisting of two subunits, ferritin light polypeptide 1 (FTL1) and ferritin heavy polypeptide 1 (FTH1), this complex forms an intricate structure 47 . It is notable that excess Fe 2+ accumulation within ferritin leads to the formation of an unstable pool of iron.…”
Section: Major Signalling Pathways Regulating Ferroptosismentioning
confidence: 99%
“…Dixon et al experimentally demonstrated that deferoxamine (DFO), an iron chelator, can target the Fenton reaction to reduce ROS production and inhibit ferroptosis (1). Intracellular excess Fe 2+ is usually stored in the form of ferritin, which contains two subunits, FTH1 (ferritin heavy chain 1) and FTL (ferritin light chain) (10). FTH1 functions to store iron.…”
Section: Accumulation Of Ironmentioning
confidence: 99%